Treading the Path of the Sharia: Indonesian Feminism at the Crossroads of Western Modernity and Islamism - Manneke Budiman (Journal of Indonesian Social Sciences and Humanities, 2008)
The downfall of Suhartos New Order in 1998 has opened up a new era of political freedom and participation for activists and for groups that try to promote emancipatory agendas as well as for political Islamists keen on introducing tougher conservative, religious measures to society. Womens activism and participation in different sectors has flourished, and their voices have had much stronger echoes in the political dynamics of the country. However, the new era has also given rise to Islamic radicalism that is also hostile to feminist causes and perceives feminism as part of the Western hegemonic project. In such a slippery political terrain, womens movements in Indonesia have to remake the image of feminism in Indonesian terms so that it cannot be dismissed as an ideology imported from the West and, simultaneously, they must develop a home-grown counter-discourse against the mainstream interpretation of sacred texts by using the same sources of knowledge that the Islamists employ. To what extent women activists have succeeded or failed in their struggles to free Indonesian Muslim women from the shackles of the male-dominated reading of Islamic dogma, and what the future trajectories of their struggles might be, are the primary concerns of this essay.